A 6-year retrospective study of fine needle aspiration cytology pattern of otorhinolaryngological cases of patients referred to national ear care centre Kaduna (2013-2018) - Rimi, Maryam Ibrahim; Iliyasu, Yawale; Mustapha Yaro, Abubakar; Isaac, Agyigra; Muhammad, Kabir (International Journal of Research in Medical Sciences, 2023)
Background: This study was carried out to obtain the retrospective study of FNAC cases referred to NECC; and review occurrences of ortorhinolaryngological swellings and demographic studies of patients for a period of 6 years (2013-2018). Records of FNAC were obtained from the laboratory department’s unit’s register alongside the biodata of patients for demographic studies. Methods: FNAC samples were treated for diagnosis according to the unit’s standard operating procedure for cytology. A total of three hundred and fifty-three 353 cases were reported and tables were then plotted to present the study cases using simple descriptive statistics. Results: Highest age distribution was between thirty to thirty-nine (30-39) years with a total of ninety-five cases 95(26.9%) followed by the range of forty to forty-nine (40-49) years with a value of eighty 80(22.6%). Females had the highest frequency of one hundred and thirty-three 133 (62.3%) compared to their male patient counterpart with a value of two hundred and twenty 220 (37.6%). The site of sample collection had ANS with the highest value of eighty-one 81 (42.4%) compared to other sites. The year 2016 had the highest number of FNAC cases and finally ninety 6 cases 96 (27.2%) of cases were inflammatory, two hundred and thirty-two 232 (65.7%) were benign while twenty five 25 (7.1%) were malignant. Conclusions: In conclusion; FNAC plays a vital role in managing otorhinolaryngology conditions and gives a way forward for effective treatment to patients and often at times is therapeutic as some patients come with fluid field swelling that get relieved after the procedure.